How to demix Alzheimer-type and PSP-type tau lesions out of their mixture -hybrid approach to dissect comorbidity- - Ebashi, Momoko (Acta Neuropathol Commun, 2019)
Neurofibrillary tangles (NFTs), are shared between progressive supranuclear palsy (PSP) and Alzheimer disease (AD). Histological distinction of PSP and AD is possible based on the distribution of NFTs. However, neuropathologists may encounter diagnostic difficulty with comorbidity of PSP and AD. In this study, we tried to circumvent this difficulty by analyzing five autopsied brains harboring both PSP and AD pathology. Tau-positive lesions were sorted based on their cell type (neuron versus glia), and tau isoforms: three-repeat (3R) versus four-repeat (4R) tau. 16 regions were selected to map these lesions throughout the brain. 4R-tau lesions were present in all areas examined. Among them, 3R-tau lesions were absent in some areas. These 4R selective (4R+/3R-) areas dictate prototypic distribution of PSP, not usually found in AD, such as pontine nucleus, red nucleus, inferior olivary nucleus, dentate nucleus, globus pallidus and putamen, each contained both glial and neuronal lesions. In contrast, additional 3R-tau lesions were found in hippocampal formation to neocortex, where 3R immunoreactivity (IR) was predominant over the 4R counterpart mainly in neurons as found in AD but not in PSP. Although tau lesions in central grey matter, substantia nigra and locus coeruleus are found in both AD and PSP, 4R-selectivity with glial component suggests PSP origin. Even if the presence of 3 R IR in these areas suggests AD pathology, it does not exclude the involvement of PSP-type lesion because distinction of 4R IR into PSP or AD is not yet possible. Further demixing may be possible if biochemical difference of 4R tau between PSP and AD is identified.